Genetic transformation of cotton with a harpin-encoding gene hpaXoo confers an enhanced defense response against different pathogens through a priming mechanism - Song Congfeng; Li Ming; Wang Xiben; Miao Weiguo; Wang Yu; Hu Dongwei; Wang Jinsheng (BMC Plant Biology, 2010)
Abstract Background The soil-borne fungal pathogen Verticillium dahliae Kleb causes Verticillium wilt in a wide range of crops including cotton (Gossypium hirsutum). To date, most upland cotton varieties are susceptible to V. dahliae and the breeding for cotton varieties with the resistance to Verticillium wilt has not been successful. Results Hpa1Xoo is a harpin protein from Xanthomonas oryzae pv. oryzae which induces the hypersensitive cell death in plants. When hpa1Xoo was transformed into the susceptible cotton line Z35 through Agrobacterium-mediated transformation, the transgenic cotton line (T-34) with an improved resistance to Verticillium dahliae was obtained. Cells of the transgenic T-34, when mixed with the conidia suspension of V. dahliae, had a higher tolerance to V. dahliae compared to cells of untransformed Z35. Cells of T-34 were more viable 12 h after mixing with V. dahliae conidia suspension. Immunocytological analysis showed that Hpa1Xoo, expressed in T-34, accumulated as clustered particles along the cell walls of T-34. In response to the infection caused by V. dahliae, the microscopic cell death and the generation of reactive oxygen intermediates were observed in leaves of T-34 and these responses were absent in leaves of Z35 inoculated with V. dahliae. Quantitative RT-PCR analysis indicated that five defense-related genes, ghAOX1, hin1, npr1, ghdhg-OMT, and hsr203J, were up-regulated in T-34 inoculated with V. dahliae. The up-regulations of these defense-relate genes were not observed or in a less extent in leaves of Z-35 after the inoculation. Conclusions Hpa1Xoo accumulates along the cell walls of the transgenic T-34, where it triggers the generation of H2O2 as an endogenous elicitor. T-34 is thus in a primed state, ready to protect the host from the pathogen. The results of this study suggest that the transformation of cotton with hpa1Xoo could be an effective approach for the development of cotton varieties with the improved resistance against soil-borne pathogens.